Incompatibilidad pre y postcigótica entre dos poblaciones de Diatraea saccharalis Fabricius, 1794 (Lepidóptera: Crambidae) de Argentina - Fogliata, Sofia Victoria (2017)
Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae) is one of the most important pests in the North ofArgentina in sugar cane and in the Pampas region is the most important pest in maize and sorghum. It is a polyphagousspecies, with bioecological characteristics that could generate a limited gene flow among the populations of the country,favoring the appearance of biotypes. Therefore, the objective of the study was to characterize the biology andreproductive compatibility of two populations collected in Buenos Aires (maize) and Tucumán (sugarcane) in Argentina.The collected larvae were kept in the laboratory under controlled conditions (25 ± 2 ºC, 75% RH, 14:10 L / O). Theparameters evaluated were: egg duration, larvae and pupa, pupae weight, adult longevity and sex ratio, number ofspermatophores, duration of periods of preoviposition, oviposition and postoviposition, fecundity and fertility. Nosignificant differences were found in biological parameters, but prezygotic and postzygotic incompatibility was detectedamong populations. This result shows an interruption of the gene flow, suggesting that the populations of Tucumán andBuenos Aires are, possibly, different biotypes. This study constitutes the first record of reproductive isolation amongpopulations of D. saccharalis from Argentina using biological parameters and reproductive compatibility, being useful todefine strategies of management and control of populations of D. saccharalis in Argentina